A kind of polyimide adhesive material and its preparation method and application

By using dianhydride monomers and diamine monomers without conjugated structures, polyimide adhesive materials with high light transmittance, low dielectric constant, low dielectric loss and low hygroscopy are prepared, which solves the problems of insufficient light transmittance and poor dielectric performance in the microelectronics industry, and meets the material needs of high-frequency communication technology.

CN115873243BActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111150206.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-29
Publication Date
2025-04-25
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

Traditional polyimide materials have insufficient light transmittance and do not meet the standards in the microelectronics industry, which cannot meet the requirements of high-frequency communication technology for low dielectric constant, low dielectric loss, and low moisture absorption materials.

Method used

By using dianhydride monomers and diamine monomers that do not contain conjugated structures or cannot form a large range of conjugated structures after polymerization, polyimide adhesive materials with high light transmittance, low dielectric constant, low dielectric loss, and low hygroscopy are prepared.

Benefits of technology

It realizes the high light transmittance and good heat resistance of polyimide materials, has low dielectric constant, low dielectric loss and low hygroscopic rate, and meets the application needs of high-frequency communication technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003286961250000031
    Figure BDA0003286961250000031
  • Figure BDA0003286961250000032
    Figure BDA0003286961250000032
  • Figure BDA0003286961250000034
    Figure BDA0003286961250000034
Patent Text Reader

Abstract

The present invention relates to a polyimide adhesive material with high light transmittance and good heat resistance and a preparation method thereof. The polyimide adhesive material is prepared from a diamine monomer and a dianhydride monomer, wherein the dianhydride monomer and the diamine monomer do not contain halogen and silicon, and the dianhydride monomer and / or the diamine monomer include a dianhydride monomer and / or a diamine monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization. The polyimide adhesive material has a total transmittance of ≥65% at 350nm to 800nm ​​in a solution state (5% wt-60% wt, 1cm optical path); after curing, it has good heat resistance, excellent high-frequency dielectric performance, low moisture absorption rate, and excellent bonding performance with substrates such as copper and silicon. It is mainly suitable for bonding electronic materials, especially bonding and packaging of flexible devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide, in particular to a polyimide adhesive material and a preparation method and application thereof. Background Art

[0002] Polyimide (PI) is a type of polymer containing an imide ring structure in the main chain of the molecule. It is one of the functional polymer materials with the best comprehensive performance and one of the few polymer materials that can meet the needs of the microelectronics industry. PI materials have always been one of the most important basic materials in the microelectronics industry. PI films and adhesives are widely used in the manufacture and packaging of microelectronic devices.

[0003] In recent years, with the rapid development of the microelectronics industry, more and more devices have put forward higher requirements on the light transmittance of materials, such as high-transmittance solar cells, transparent display technology, etc. However, due to the charge transfer complex, most traditional polyimide materials have insufficient light transmittance, which limits their application in new light-transmitting microelectronic devices. In addition, in order to ensure the stability of the device during processing, especially the stability between different interfaces, the heat resistance of the adhesive material is also crucial. Specifically, since the packaging and processing of electronic devices may include long-term (~1h) high-temperature treatment steps, it is usually required that the adhesive material has a high glass transition temperature (T g ).

[0004] At the same time, with the gradual application and promotion of 5G technology, high-frequency communication technology with ultra-high speed and ultra-high data density will be fully rolled out. Ensuring high-fidelity transmission of electromagnetic waves within the millimeter wave frequency range is a great challenge for the manufacture of electronic devices, especially dielectric materials for signal receiving and transmission components such as antennas. According to the principles of electromagnetics, the higher the frequency of electromagnetic waves, the higher their energy, the stronger their penetration, the higher their penetration loss, and the weaker their diffraction ability. Traditional epoxy resin and PI adhesive materials have problems with high dielectric constant, dielectric loss and hygroscopicity, and can no longer meet the application requirements of high-frequency and high-speed communications in the 5G era. Therefore, it is urgent to develop new adhesive materials with low dielectric constant, low dielectric loss and low moisture absorption to meet the technical requirements of high-frequency communications. Summary of the invention

[0005] The present invention provides a polyimide adhesive material with high light transmittance and high bonding strength. At the same time, the polyimide adhesive material provided by the present invention has the characteristics of low moisture absorption rate, low dielectric constant and low dielectric loss. It solves the problem that the adhesive materials in the current traditional microelectronics industry have insufficient light transmittance and substandard dielectric properties and cannot be applied to transparent microelectronic devices and high-frequency communication technologies.

[0006] One of the purposes of the present invention is to provide a polyimide adhesive material prepared from a diamine monomer and a dianhydride monomer, wherein the dianhydride monomer and the diamine monomer do not contain halogen (such as fluorine) and silicon, and the dianhydride monomer and / or the diamine monomer include dianhydride monomers and / or diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization.

[0007] In the technical solution of the present invention, preferably, the total amount of dianhydride monomers and diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is ≥ 35 mol% of the total amount of monomers, and more preferably, the total amount of dianhydride monomers and diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is ≥ 38 mol% of the total amount of monomers. The above total amount of monomers is the total amount of all dianhydride monomers and diamine monomers.

[0008] In the technical solution of the present invention, preferably, the dianhydride monomer and / or diamine monomer includes at least one aromatic dianhydride and / or aromatic diamine monomer, wherein the total amount of the aromatic dianhydride and aromatic diamine monomer is ≥ 30 mol% of the total amount of monomers, more preferably ≥ 35 mol% of the total amount of monomers.

[0009] It is generally believed that the formation of charge transfer complexes is the main reason for the poor light transmittance of polyimide materials. The present invention reduces the formation of intra-chain / inter-chain charge transfer complexes by breaking the formation of large-scale long-chain conjugated structures and limiting the alternating electron-deficient / electron-rich structures, thereby improving the light transmittance of the material. Specifically, the diamine monomer and / or dianhydride monomer preferably does not contain a monomer having a conjugated structure or a monomer that cannot form a large-scale conjugated structure after polymerization, and the total amount of such dianhydride monomers plus diamine monomers is ≥ 35% (molar percentage) of the total amount of monomers; at the same time, in order to ensure the heat resistance of the cured material, the dianhydride monomer and / or diamine monomer preferably includes at least one aromatic monomer.

[0010] The dianhydride monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization has a structure as shown in (1):

[0011]

[0012] Wherein X is a structure that cannot form a continuous π-π / p-π conjugated system with two anhydride structures, such as but not limited to:

[0013] wait.

[0014] The diamine monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization has a structure as shown in formula (2):

[0015]

[0016] Wherein Y is a structure that cannot form a continuous π-π / p-π conjugated system with two amine groups, such as but not limited to:

[0017] Etc. Among them In the formula, two amine groups are connected at any two sites, and the remaining two sites are connected to alkyl groups; In the above, the number of methylene groups in the four segments is not zero at the same time.

[0018] The aromatic dianhydride or diamine monomer has the general structural formula (3):

[0019]

[0020] Wherein m is an amine or anhydride structure; n is a structure containing aromatic chemical structures such as benzene, naphthalene, anthracene, fluorene, pyridine, furan, thiazole, pyrimidine and other structural units. Such monomers include but are not limited to pyromellitic anhydride, biphenyltetracarboxylic anhydride, 4,4'-biphenyl ether anhydride, p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl and the like.

[0021] According to many reports, the light transmittance of polyimide materials can be significantly improved by introducing fluorine-containing structural units or mixed doping of fluorine-containing materials, while improving its dielectric properties and reducing the material's moisture absorption rate. However, due to the low surface energy of fluorine-containing materials, their peel strength with other materials including copper is poor, and therefore they are not suitable for microelectronic adhesive materials. The polyimide adhesive material provided by the present invention is preferably formed by polymerization of fluorine-free monomers, and has good bonding strength with various materials.

[0022] At the same time, there are literature and patent data reporting that the bonding effect of polyimide materials can be improved by introducing structural units containing dimethylsiloxane segments, but since the polydimethylsiloxane molecular segments have large losses under the alternating electric field, it is easy to cause the final material to have high dielectric loss under high frequency. The polyimide adhesive material provided by the present invention is preferably formed by polymerization of monomers that do not contain silicon, and has the characteristics of low moisture absorption rate, low dielectric constant, and low dielectric loss. At the same time, since segment units that cannot form a large-scale conjugated structure are embedded in the polyimide macromolecular segment, the activity of the molecular segment is improved, and while having excellent dielectric properties, good substrate bonding strength is maintained, solving the problem that the dielectric properties of adhesive materials in the current traditional microelectronics industry are not up to standard and cannot be applied to high-frequency communication technology.

[0023] The polyimide adhesive material of the present invention has a visible light transmittance (total transmittance of 350nm to 800nm) of ≥65% in solution state (5%wt-60%wt, 1cm optical path) and preferably 70% to 95%.

[0024] The polyimide adhesive material of the present invention has an ultraviolet light transmittance (total transmittance of 200nm to 350nm) of ≤35% in its solution state (5%wt-60%wt, 1cm optical path) and preferably ≤25%.

[0025] The polyimide adhesive material of the present invention has a yellowness index of ≤0.45, preferably ≤0.40, in its solution state (50 uM liquid film).

[0026] The polyimide adhesive material of the present invention has a yellowness index of ≤0.50, preferably ≤0.45 after being cured (25uM polyimide film).

[0027] The polyimide adhesive material of the present invention has a glass transition temperature (T g )≥190°C, preferably ≥200°C.

[0028] The polyimide adhesive material of the present invention has a peel strength of ≥10N / cm, preferably ≥12N / cm, with metal conductive materials such as copper foil and semiconductor substrates such as silicon after curing; a peel strength of ≥10N / cm, preferably ≥12N / cm, with polymer substrates such as Kapton film and Upilex film; and a peel strength of ≥10N / cm, preferably ≥12N / cm, with inorganic substrates such as glass and ceramics (including molded profiles, sheets, and fiber braids, etc.).

[0029] The polyimide adhesive material of the present invention has a dielectric constant of ≤3.1, preferably ≤3.0, and a dielectric loss of ≤0.010, preferably ≤0.008 at 10 GHz after being cured.

[0030] The polyimide adhesive material of the present invention has a moisture absorption rate of ≤1.0%, preferably ≤0.8%, after being cured.

[0031] The ratio of the dielectric constant of the polyimide adhesive material at 10 GHz after humidity conditioning at 25° C. and 65% humidity for 72 hours to the dielectric constant at 10 GHz after drying in a vacuum oven at 100° C. for 48 hours is 1.00-1.15.

[0032] The second object of the present invention is to provide a method for preparing the polyimide adhesive material, comprising polymerizing a diamine monomer and a dianhydride monomer to obtain a polyamic acid solution; then directly using the polyamic acid solution for processing adhesives and then imidizing, or imidizing the polyamic acid solution and then using it for processing adhesives.

[0033] The dianhydride monomers and / or diamine monomers include dianhydride monomers and diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization. Preferably, the total amount of the dianhydride monomers and diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is ≥ 35 mol% of the total amount of monomers.

[0034] Preferably, the dianhydride monomer and / or diamine monomer comprises at least one aromatic dianhydride and / or aromatic diamine monomer. The total amount of the aromatic dianhydride and aromatic diamine monomers is ≥ 30 mol% of the total amount of monomers.

[0035] The dianhydride monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization has a structure shown in formula (1), and the diamine monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization has a structure shown in formula (2).

[0036] In the preparation method of the present invention, the diamine monomer is, for example, selected from at least one of p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 1,6-hexamethylenediamine (hexamethylenediamine), and 2,2-bis[4-(4-aminophenoxy)phenyl]propane, but is not limited to the above diamines.

[0037] In the preparation method of the present invention, the dianhydride monomer is, for example, at least one selected from pyromellitic dianhydride, biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, and 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride), but is not limited to the above dianhydrides.

[0038] In the preparation method of the present invention, the ratio of the total molar amount of the dianhydride monomer to the total molar amount of the diamine monomer is preferably (0.80:1.00) to (0.99:1.00).

[0039] In the preparation method of the present invention, the polymerization reaction uses an aprotic solvent as a reaction medium, and the polymerization reaction temperature is 0 to 90°C, for example, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, etc.

[0040] In the preparation method of the present invention, there is no particular limitation on the aprotic solvent, which is a common solvent for polymerization reactions in the art, such as N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone and other aprotic solvents.

[0041] In the preparation method of the present invention, the total weight of the diamine monomer and the dianhydride monomer accounts for 5-50% of the weight of the reaction system.

[0042] The reaction system comprises a reaction medium and reactants (diamine monomer and dianhydride monomer).

[0043] The preparation method of the present invention may further include adding a common end-capping agent, such as maleic anhydride, phthalic anhydride, etc., and the amount used is the common amount used in the polymerization method in the art.

[0044] The polyimide adhesive material is a solid polyimide / polyimide polyamic acid adhesive material, or a polyimide / polyimide polyamic acid adhesive sheet / film.

[0045] The preparation method of the present invention polymerizes diamine monomers and dianhydride monomers and possible end-capping agents to obtain a polyamic acid solution. The solution can be directly used for the next step of processing and gluing; it can also be formed into a polyimide solution or a partially imidized polyimide polyamic acid solution by imidization methods such as thermal imidization or chemical imidization, and the solution can be directly used for the next step of processing and gluing, or solid polyimide / polyimide polyamic acid adhesive materials can be obtained by separation means such as precipitation and subsequent drying; or the solvent is partially removed to form a polyimide / polyimide polyamic acid adhesive sheet / film. The above all adopt the common methods in the field, and the specific use method is not limited in this patent.

[0046] The third object of the present invention is to provide a polyimide adhesive material obtained by the preparation method.

[0047] A fourth object of the present invention is to provide the application of the polyimide adhesive material or the polyimide adhesive material obtained by the preparation method in photovoltaic energy materials, transparent display materials, and high-frequency communication materials.

[0048] The polyimide adhesive material obtained by the present invention has high light transmittance and good heat resistance. In the solution state (5%wt-60%wt, 1cm optical path), the total transmittance of 350nm-800nm ​​is ≥65%; after curing, it has good heat resistance, excellent high-frequency dielectric performance, low moisture absorption rate, and excellent bonding performance with substrates such as copper and silicon. It is mainly suitable for bonding electronic materials, especially bonding and packaging of flexible devices. DETAILED DESCRIPTION

[0049] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0050] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0051] Preparation of polyamic acid adhesive:

[0052] First, a non-protonic solvent such as N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide and N-methyl-2-pyrrolidone is used as a reaction medium, and a diamine monomer and a dianhydride monomer are used as reactants to form a polyamic acid solution. The reaction temperature is 0-90°C, wherein the weight of the diamine and the dianhydride accounts for 5% to 55% of the total weight including the reaction medium and the reactants. The solution can be directly used for bonding by coating and then imidization.

[0053] Preparation of polyimide adhesive:

[0054] First, a non-protonic solvent such as N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide and N-methyl-2-pyrrolidone is used as a reaction medium, and a diamine monomer and a dianhydride monomer are used as reactants to form a polyamic acid solution, and then a polyimide solution with different imidization degrees is formed by direct heating or adding a chemical imidization agent. The solution can be directly used for bonding by coating. It is also possible to obtain polyimide adhesive powder or blocks by adding a precipitant such as ethanol and then separating and drying, and prepare a polyimide adhesive liquid by re-dissolving.

[0055] Preparation of polyamic acid adhesive film:

[0056] The prepared polyamic acid adhesive liquid is cast and the solvent is volatilized to form a film, so as to form a polyamic acid adhesive film, which can be directly used for hot pressing bonding.

[0057] Preparation of polyimide adhesive film:

[0058] The prepared polyimide adhesive liquid is cast and the solvent is volatilized to form a film, so as to form a polyimide adhesive film, which can be directly used for hot pressing bonding.

[0059] Embodiment 1:

[0060] 17.2206 g (0.0860 mol) of 4,4'-diaminodiphenyl ether (ODA) and 100 g of N,N-dimethylacetamide (DMAc) were added to a three-necked flask, and after stirring to dissolve, 42.9925 g (0.0826 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) was added, and the reaction was stirred at 80°C under nitrogen protection for 12 hours to obtain the polyamic acid adhesive solution of [Example 1]

[0061] After coating the above polyamic acid solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent was first removed at 80°C under nitrogen protection, and then the temperature was gradually raised to 200°C under nitrogen protection to complete imidization, thereby obtaining a multilayer composite structure prepared using the polyamic acid adhesive solution of [Example 1].

[0062] Embodiment 2:

[0063] The preparation process of the polyamic acid solution is exactly the same as that of [Example 1]. The solution is cast and most of the solvent is removed under nitrogen protection at 100°C to form the polyamic acid adhesive film of [Example 2].

[0064] The multilayer composite structure prepared by the polyamic acid adhesive film of [Example 2] is formed by hot roller lamination or flat plate hot pressing at 280°C with copper foil, silicon wafer, Kapton and Upilex film.

[0065] Embodiment 3:

[0066] The preparation process of the polyamic acid solution is exactly the same as that of [Example 1]. The solution is heated to 150° C. and refluxed for 12 hours to obtain the polyimide adhesive solution of [Example 3].

[0067] After coating the above polyimide solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent was first removed at 60°C under nitrogen protection, and then the temperature was gradually increased to 180°C under nitrogen protection to completely dry and solidify, thereby obtaining a multilayer composite structure prepared using the polyimide adhesive solution of [Example 3].

[0068] Embodiment 4:

[0069] The preparation process of the polyimide solution is exactly the same as that of [Example 3]. The solution is cast and most of the solvent is removed under nitrogen protection at 200°C to form the polyimide adhesive film of [Example 4].

[0070] The multilayer composite structure prepared by the polyimide adhesive film of [Example 4] is formed by 300° C. hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton and Upilex film.

[0071] Embodiment 5:

[0072] 11.0132 g (0.0550 mol) of 4,4' diaminodiphenyl ether (ODA), 6.9392 g (0.0350 mol) of diaminodiphenylmethane (MDA) and 257 g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and after stirring to dissolve, 46.3757 g (0.0891 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) was added, and the reaction was stirred at 20°C under nitrogen protection for 24 hours to obtain [Example 5] polyamic acid adhesive.

[0073] After coating the above polyamic acid solution on copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth, most of the solvent is first removed at 120°C under nitrogen protection, and then the temperature is gradually increased to 280°C under nitrogen protection to complete imidization, thereby obtaining a multilayer composite structure prepared using the polyamic acid adhesive solution of [Example 5].

[0074] Embodiment 6:

[0075] 3.2442g (0.0300mol) of p-phenylenediamine (PDA), 1.1621g (0.0100mol) of hexamethylenediamine (HDA) and 160g of N,N-dimethylformamide (DMF) were added to a three-necked flask, and 20.7155g (0.0398mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) was added after stirring and dissolving, and stirred and reacted at 40°C under nitrogen protection for 18 hours to obtain the polyamide acid solution of [Example 6]. The solution was then heated to 160°C and refluxed for 8 hours to obtain the polyimide adhesive solution of [Example 6]. The solution was cast and most of the solvent was removed under the conditions of 180°C and nitrogen protection to form the polyimide adhesive film of [Example 6].

[0076] A multilayer composite structure prepared by the polyimide adhesive film of [Example 6] is formed with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth by 350°C hot roller lamination or flat plate hot pressing.

[0077] Embodiment 7:

[0078] 32.8400g (0.0800mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 55g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and 10.0335g (0.0460mol) of pyromellitic dianhydride (PMDA) and 13.5326g (0.0260mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) were added after stirring and dissolving, and stirred at 90°C for 6 hours under nitrogen protection to obtain [Example 7] polyamic acid solution. The solution was cast and most of the solvent was removed under 200°C and nitrogen protection to form [Example 7] polyamic acid adhesive film.

[0079] A multilayer composite structure prepared by the polyamic acid adhesive film of [Example 7] is formed by 380°C hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth.

[0080] Embodiment 8:

[0081] 5.5272g (0.0300mol) of 4,4'-diaminobiphenyl (BzD), 4.1051g (0.0100mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 115g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and after stirring and dissolving, 5.9562g (0.0192mol) of 4,4'-biphenyl ether dianhydride (ODPA) and 10.4097g (0.0200mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) were added, and the mixture was stirred and reacted at 15°C under nitrogen protection for 12 hours to obtain a polyamic acid solution of [Example 8]. The solution was then heated to 200°C and refluxed for 6 hours to obtain a polyimide adhesive solution of [Example 8]. The solution was cast and most of the solvent was removed at 240° C. under nitrogen protection to form the polyimide adhesive film [Example 8]

[0082] A multilayer composite structure prepared by the polyimide adhesive film of [Example 8] is formed by 330°C hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth.

[0083] Embodiment 9:

[0084] The preparation process of the polyimide solution is exactly the same as that of Example 8, and then 0.1569 g (0.0016 mol) of maleic anhydride is added and stirred at 25°C for 3 hours under nitrogen protection to obtain the polyimide adhesive solution of Example 9. The solution is cast and most of the solvent is removed under nitrogen protection at 240°C to form the polyimide adhesive film of Example 9.

[0085] A multilayer composite structure prepared by the polyimide adhesive film of [Example 9] is formed with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth by 330°C hot roller lamination or flat plate hot pressing.

[0086] Embodiment 10:

[0087] 10.4589g (0.0900mol) of hexamethylenediamine (HDA) and 112g of N,N-dimethylacetamide (DMAc) were added to a three-necked flask, and 16.5034g (0.0532mol) of 4,4'-biphenyl ether dianhydride (ODPA) and 10.2977g (0.0350mol) of biphenyltetracarboxylic dianhydride (BPDA) were added after stirring and dissolving, and stirred at 50°C under nitrogen protection for 12 hours, and then the solution was heated to 200°C and refluxed for 6 hours to obtain [Example 10] polyimide adhesive solution. The solution was cast and most of the solvent was removed under 220°C and nitrogen protection to form [Example 10] polyimide adhesive film.

[0088] A multilayer composite structure prepared by the polyimide adhesive film of [Example 10] is formed by 370°C hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth.

[0089] Embodiment 11:

[0090] The preparation process of the polyimide solution is exactly the same as that of Example 10. The polyimide adhesive material powder of Example 11 is obtained by adding ethanol for precipitation and then drying at 200°C, and then dissolved in a 50 / 50 ethyl acetate / DMAc mixed solution to form a polyimide adhesive solution of Example 11 with a solid content of 7.5%.

[0091] After coating the above polyimide solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent was first removed at 60°C under nitrogen protection, and then gradually heated to 300°C under nitrogen protection to completely dry and solidify, thereby obtaining a multilayer composite structure prepared using the polyimide adhesive solution of [Example 11].

[0092] Embodiment 12:

[0093] The preparation process of the polyimide solution is exactly the same as that of [Example 10], and then 0.2370 g (0.0016 mol) of phthalic anhydride is added and stirred at 25°C under nitrogen protection for 3 hours to obtain the polyimide adhesive solution of [Example 12]. The solution is cast and most of the solvent is removed under nitrogen protection at 220°C to form the polyimide adhesive film of [Example 12].

[0094] A multilayer composite structure prepared by the polyimide adhesive film of [Example 12] is formed with copper foil, silicon wafer, Kapton, Upilex film and quartz fiber cloth by 370°C hot roller lamination or flat plate hot pressing.

[0095] Comparative Example 1:

[0096] 17.2206 g (0.0860 mol) of 4,4' diaminodiphenyl ether (ODA) and 240 g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and after stirring to dissolve, 24.9204 g (0.0847 mol) of biphenyltetracarboxylic dianhydride (BPDA) was added, and the mixture was stirred and reacted at 25°C under nitrogen protection for 12 hours to obtain [Comparative Example 1] polyamic acid adhesive.

[0097] After coating the above polyamic acid solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent is first removed at 200°C under nitrogen protection, and then the temperature is gradually increased to 400°C under nitrogen protection to complete imidization, thereby obtaining a multilayer composite structure prepared using the polyamic acid adhesive of [Comparative Example 1].

[0098] Comparative Example 2:

[0099] The preparation process of the polyamic acid solution is exactly the same as that of [Comparative Example 1]. The solution is heated to 200° C. and refluxed for 12 hours to obtain the polyimide adhesive solution of [Comparative Example 2].

[0100] After coating the above polyimide solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent was first removed at 200°C under nitrogen protection, and then the temperature was gradually increased to 300°C under nitrogen protection to completely dry and solidify, thereby obtaining a multilayer composite structure prepared using the polyimide adhesive of [Comparative Example 2].

[0101] Comparative Example 3:

[0102] 16.0032g (0.0800mol) of 4,4'-diaminodiphenyl ether (ODA) and 140g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and after stirring and dissolving, 24.3212g (0.0784mol) of 4,4'-biphenyl ether dianhydride (ODPA) was added, and stirred and reacted at 50°C under nitrogen protection for 6 hours to obtain [Comparative Example 3] polyamic acid solution. The solution was cast and most of the solvent was removed under 220°C and nitrogen protection to form [Comparative Example 3] polyamic acid adhesive film.

[0103] A multilayer composite structure prepared by the polyimide adhesive film of [Comparative Example 3] is formed by 370° C. hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton and Upilex film.

[0104] Comparative Example 4:

[0105] The preparation process of the polyamic acid solution is exactly the same as that of [Comparative Example 3]. The solution is heated to 220°C and refluxed for 8 hours to obtain [Comparative Example 4] polyimide adhesive jelly. The solution is cast at 80°C and most of the solvent is removed at 200°C under nitrogen protection to form [Comparative Example 4] polyimide adhesive film.

[0106] A multilayer composite structure prepared by the polyimide adhesive film of [Comparative Example 4] is formed by 380°C hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton and Upilex film.

[0107] Comparative Example 5:

[0108] In a three-necked flask, 11.898 g (0.0600 mol) of diaminodiphenylmethane (MDA), 6.4046 g (0.0200 mol) of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl (TFDB) and 110 g of N,N-dimethylacetamide (DMAc) were added, and after stirring to dissolve, 41.2228 g (0.0792 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) was added, and the reaction was stirred at 60°C under nitrogen protection for 12 hours to obtain [Comparative Example 5] polyamic acid adhesive.

[0109] After coating the above-mentioned polyamic acid adhesive on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent is first removed at 130°C under nitrogen protection, and then the temperature is gradually increased to 280°C under nitrogen protection to complete imidization, thereby obtaining a multilayer composite structure prepared using the polyamic acid adhesive of [Comparative Example 5].

[0110] Comparative Example 6:

[0111] The preparation process of the polyamic acid solution is exactly the same as that of [Comparative Example 5]. The solution is cast and most of the solvent is removed under the conditions of 150°C and nitrogen protection to form the polyamic acid adhesive film of [Comparative Example 6].

[0112] A multilayer composite structure prepared by the polyamic acid adhesive film of [Comparative Example 6] is formed by 350°C hot roller lamination or flat plate hot pressing with copper foil, silicon wafer, Kapton and Upilex film.

[0113] Comparative Example 7:

[0114] 15.2182 g (0.0760 mol) of 4,4' diaminodiphenyl ether (ODA), 3.7277 g (0.0150 mol) of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 150 g of N,N-dimethylacetamide (DMAc) were added to a three-necked flask, and after stirring and dissolving, 45.4908 g (0.0874 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) was added, and the reaction was stirred at 90 ° C under nitrogen protection for 6 hours, and then the temperature was raised to 160 ° C and refluxed for 8 hours to obtain [Comparative Example 7] polyimide adhesive.

[0115] After coating the above polyimide solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent is first removed at 100°C under nitrogen protection, and then gradually heated to 250°C under nitrogen protection to completely dry and solidify, thereby obtaining a multilayer composite structure prepared using the polyimide adhesive of [Comparative Example 7].

[0116] Comparative Example 8:

[0117] The preparation process of the polyimide solution is exactly the same as that of [Comparative Example 7]. The solution is cast and most of the solvent is removed under the conditions of 150°C and nitrogen protection to form the polyimide adhesive film of [Comparative Example 8].

[0118] A multilayer composite structure prepared by the polyimide adhesive film of [Comparative Example 8] is formed by hot roller lamination or flat plate hot pressing at 280°C with copper foil, silicon wafer, Kapton and Upilex film.

[0119] Comparative Example 9:

[0120] In a three-necked flask, 20.0364 g (0.1000 mol) of dodecanediamine (DDA) and 110 g of N,N-dimethylacetamide (DMAc) were added, and after stirring to dissolve, 10.0877 g (0.0450 mol) of 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride (HPMDA) and 13.9597 g (0.0450 mol) of 4,4'-biphenyl ether dianhydride (ODPA) were added, and the mixture was stirred and reacted at 80 ° C. under nitrogen protection for 4 hours, and then the temperature was raised to 160 ° C. and refluxed for 5 hours to obtain [Comparative Example 9] polyimide adhesive.

[0121] After coating the above polyimide solution on copper foil, silicon wafer, Kapton and Upilex film, most of the solvent is first removed at 100°C under nitrogen protection, and then gradually heated to 230°C under nitrogen protection to completely dry and solidify, thereby obtaining a multilayer composite structure prepared using the polyimide adhesive of [Comparative Example 9].

[0122] Test Method

[0123] Transmittance test: TU-1901 double-beam UV-visible spectrophotometer (Beijing Puxi General Instrument Co., Ltd.) and 1 cm optical path quartz cuvette were used for testing.

[0124] Yellowness test: UltraScan VIS system (HunterLab) was used for testing.

[0125] Bond strength test: According to IPC-TM-650-2.4.9 standard, the Free Wheeling Rotary Drum test fixture is used to perform peel strength tests on cured polyimide adhesive materials and copper, Kapton, Upilex, and quartz fiber cloth laminated structures; the Sliding Plate test fixture is used to perform peel strength tests on cured polyimide adhesive materials and silicon laminated structures.

[0126] Glass transition temperature test: A thermomechanical analyzer was used to test the completely cured adhesive film at a load of 0.05N and a heating rate of 10°C / min.

[0127] Dielectric constant and dielectric loss: According to IPC-TM-650-2.5.5.9 standard, the resonant cavity method was used to test the cured polyimide adhesive film at 10 GHz and 30 GHz.

[0128] Moisture absorption rate: The moisture absorption rate of the prepared cured polyimide adhesive material film was tested according to the IPC-TM-650-2.6.2 standard.

[0129] The test results of the above embodiments and comparative examples are shown in Table 1: Summary of test results.

[0130] Table 1

[0131]

[0132] It can be seen from Examples 1 to 12 that the polyimide adhesive material prepared by the technology of the present invention, whether in the form of polyamic acid or polyimide adhesive liquid, or in the form of polyamic acid or polyimide adhesive film, has the characteristics of high light transmittance, low dielectric constant and dielectric loss, low moisture absorption rate, high adhesion and high heat resistance.

[0133] In contrast, common polyimide materials, such as Comparative Examples 1 to 4, have poor light transmittance due to the strong charge transfer complex effect, and have the disadvantage of high moisture absorption of traditional polyimide.

[0134] As disclosed in many literatures, by adding fluorine-containing monomer fragments, the transmittance and dielectric properties of polyimide materials can be greatly improved and the moisture absorption rate can be reduced. However, due to the low surface energy of fluorine-containing materials, their peel strength with many materials including copper, silicon, Kapton, and Upilex is low (Comparative Examples 5 and 6), and therefore they are not suitable as adhesive materials.

[0135] Literature reports that adding siloxane segments can improve the bonding performance of the material while also providing better light transmittance, which is consistent with the test results of Comparative Examples 7 and 8. However, since the siloxane segments are too flexible and have large losses at high frequencies, they are not suitable for packaging and bonding high-frequency communication electronic devices.

Claims

1. A polyimide adhesive material prepared from a diamine monomer and a dianhydride monomer, wherein: The dianhydride monomer and the diamine monomer do not contain halogen and silicon, the dianhydride monomer and / or the diamine monomer include dianhydride monomers and / or diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization, and the dianhydride monomers and / or the diamine monomers include at least one aromatic dianhydride and / or aromatic diamine monomer; the total amount of the dianhydride monomers and the diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is ≥ 35 mol% of the total amount of monomers, and the total amount of the aromatic dianhydride and the aromatic diamine monomers is ≥ 30 mol% of the total amount of monomers; The dianhydride monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride); The diamine monomer that does not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is selected from at least one of 4,4'-diaminodiphenylmethane and 1,6-hexanediamine; The polyimide adhesive material is prepared from diaminodiphenylmethane, 4,4'-diaminodiphenyl ether and 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), and is prepared from hexamethylenediamine, p-phenylenediamine and 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride).

2. The polyimide adhesive material according to claim 1, characterized in that: The total amount of the dianhydride monomers and diamine monomers that do not contain a conjugated structure or cannot form a large-scale conjugated structure after polymerization is ≥ 38 mol% of the total amount of monomers.

3. The polyimide adhesive material according to claim 1, characterized in that: The total amount of aromatic dianhydride and aromatic diamine monomers is ≥ 35 mol% of the total amount of monomers.

4. The polyimide adhesive material according to claim 1, characterized in that: The polyimide adhesive material has a visible light transmittance of 5% wt to 60% wt and a light path length of 1 cm, that is, a total transmittance of 350nm to 800nm ​​of ≥65% in a solution state; and / or, The polyimide adhesive material has an ultraviolet light transmittance of 5% wt to 60% wt and a light path length of 1 cm, that is, a total transmittance of 200nm to 350nm of ≤35% in a solution state; and / or, The polyimide adhesive material has a yellowness index of ≤0.45 in a solution state and a 50 uM liquid film.

5. The polyimide adhesive material according to claim 1, characterized in that: The polyimide adhesive material has a visible light transmittance of 70% to 95% under the conditions of 5% wt to 60% wt and 1 cm optical path, i.e., a total transmittance of 350nm to 800nm; and / or, The polyimide adhesive material has an ultraviolet light transmittance of 5%wt to 60%wt and a light path length of 1 cm, that is, a total transmittance of 200nm to 350nm of ≤25% in a solution state; and / or, The polyimide adhesive material has a yellowness index of ≤0.40 in a solution state and a 50 uM liquid film.

6. The polyimide adhesive material according to claim 1, characterized in that: The glass transition temperature of the polyimide adhesive material after curing is ≥190°C; and / or, The polyimide adhesive material has a peel strength of ≥10N / cm with a metal conductive material or a silicon semiconductor substrate after curing; a peel strength of ≥10N / cm with a polymer substrate; and a peel strength of ≥10N / cm with an inorganic substrate; and / or, After the polyimide adhesive material is cured, the dielectric constant at 10 GHz is ≤3.1; the dielectric loss is ≤0.010; and / or, The moisture absorption rate of the polyimide adhesive material after curing is ≤1.0%; and / or, After the polyimide adhesive material is cured, the ratio of the dielectric constant at 10 GHz after humidity conditioning at 25° C. and 65% humidity for 72 hours to the dielectric constant at 10 GHz after drying in a vacuum oven at 100° C. for 48 hours is 1.00-1.

15.

7. The polyimide adhesive material according to claim 6, characterized in that: The polyimide adhesive material has a glass transition temperature of ≥200°C after curing; and / or, The polyimide adhesive material has a peel strength of ≥12N / cm with a metal conductive material or a silicon semiconductor substrate after curing; a peel strength of ≥12N / cm with a polymer substrate; and a peel strength of ≥12N / cm with an inorganic substrate; and / or, After the polyimide adhesive material is cured, the dielectric constant at 10 GHz is ≤3.0; the dielectric loss is ≤0.008; and / or, The moisture absorption rate of the polyimide adhesive material after curing is ≤0.8%.

8. The method for preparing a polyimide adhesive material according to any one of claims 1 to 7, comprising polymerizing a diamine monomer and a dianhydride monomer to obtain a polyamic acid solution; then directly using the polyamic acid solution for processing adhesives and then imidizing it, or imidizing the polyamic acid solution and then using it for processing adhesives.

9. The method for preparing a polyimide adhesive material according to claim 8, characterized in that: The polymerization reaction uses an aprotic solvent as a reaction medium, and the polymerization reaction temperature is 0 to 90° C.; and / or, The ratio of the total molar amount of dianhydride monomers to the total molar amount of diamine monomers is (0.80:1.00) to (0.99:1.00); and / or, The total weight of the diamine monomer and the dianhydride monomer accounts for 5-55% of the weight of the reaction system.

10. The method for preparing a polyimide adhesive material according to claim 8, characterized in that: The polyimide adhesive material is a solid polyimide / polyimide polyamic acid adhesive material, or a polyimide / polyimide polyamic acid adhesive sheet / film.

11. The polyimide adhesive material obtained according to the preparation method according to any one of claims 8 to 10.

12. Use of the polyimide adhesive material according to any one of claims 1 to 7 or the polyimide adhesive material obtained by the preparation method according to any one of claims 8 to 10 in photovoltaic energy materials, transparent display materials, and high-frequency communication materials.

Citation Information

Patent Citations

  • A preparation method of gum-free flexible copper-coating plate

    CN101157077A

  • Low-dielectric adhesive, film-like bonding agent, and adhesive laminate

    JP2003147320A

  • Polyimide resin composition and polyimide varnish

    JP2018044180A

  • Low-melt poly(amic acids) and polyimides and their uses

    US9365756B1

  • Polyimide, polyamic acid, resin solution, coating agent, and polyimide film

    WO2020141614A2